Child sexual abuse and the Catholic Church gender, power, and organizational culture - Keenan, Marie (New York : Oxford University Press, 2011)
Linking the personal and the institutional, the author locates the problem of child sexual abuse not just in individual pathology, but also within larger systemic factors, such as the very institution of priesthood itself, the Catholic take on sexuality, clerical culture, power relations, governance structures of the Catholic Church, the process of formation for priesthood and religious life, and the complex manner in which these factors coalesce to create serious institutional risks for boundary violations, including child sexual abuse.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Child sexual abuse by clergy; Child sexual abuse by clergy -- Case studies; Catholic Church -- Clergy -- Sexual behavior; Catholic Church -- Clergy -- Sexual behavior -- Case studies; Catholic Church -- Discipline; Child sexual abuse -- Religious aspects -- Catholic Church